An ultrafast, high capacity and superior longevity Ni/Zn battery constructed on nickel nanowire array film. (December 2016) - Xu, Chao; Liao, Jie; Yang, Cheng; Wang, Ruozheng; Wu, Dang; Zou, Peichao; Lin, Ziyin; Li, Baohua; Kang, Feiyu; Wong, Ching-Ping
Abstract: With the bloom of portable and wearable electronics, electrochemical storage devices featured with high performance, low-cost, safe, environmental-friendly, lightweight, thin and flexible features become more important than ever. Here, we construct a rechargeable Ni/Zn battery with a Co-doped Ni(OH)2 (CNH) and Zn materials on nickel nanowire arrays (NNA) for electrodes. The CNH cathodic material can be electrochemically deposited onto the NNA, which can deliver a high capacity of 346 mA h g −1 at current density of 5 A g −1 . Co doping can effectively stabilize Ni(OH)2 with only 10% capacity loss over 5 000 charge/discharge cycles at 30 A g −1 . For anode, the design of Zn on NNA considerably lowers the risk of corrosion and dendrite form ation. As a result, ultrafast rechargeable Ni/Zn batteries are obtained, exhibiting a cell voltage of 1.75 V, energy density of 148.54 Wh kg −1 (4.05 Wh L −1 ) and power density of 1.725 kW kg −1 (based on the mass of active materials) with a charging time of <1 min. Additionally, the NNA-based aqueous Ni/Zn battery exhibits superior longevity (only 12% capacity losses after 5000 cycles). These features enable our Ni/Zn batteries a highly promising candidate for the next generation of flexible energy storage systems. Graphical abstract: Poor cycle stability has been commonly considered as a key short slab for the aqueous alkaline batteries. In this manuscript, we constructed Co doped Ni(OH)2 and Zn on the Ni nanowire array scaffolds as the cathode and anode materials respectively, for the rechargeable Ni/Zn battery. The Ni/Zn battery can deliver high capacity, fast-charge and superior longevity, which render it promising candidate for the next generation of safe and sustainable energy storage devices. Highlights: Co-doped Ni hydroxide (CNH) nanostructure is synthesized via a simple electrodeposition process. Proper dopant degree ( 7 at% Co in the mixed metal hydroxide) can considerably enhance the cycling performance of Ni(OH)2 . The Ni nanowire array (NNA) scaffold is used as conductive supporting for the CNH, and thus the surface convexity and the highly effective ion and electron transport "high-ways" by this design can help release the stress during cycling process and improve the electrochemical performance of CNH. Zn is electrodeposited on NNA as anode for the Ni/Zn alkaline battery, where the formation of Zn dendrite is considerably suppressed. The NNA based Ni/Zn alkaline battery exhibits several features such as fast-charge rate (charged within 1 min), high-energy density (as high as 4.05 Wh L −1 ), excellent longevity (5000 cycles with 12% capacitance loss) and flexibility.